The effects of reinforced cellulose nanocrystals from sugarcane bagasse fiber on the hardness of glass ionomer cements - Hernindya Dwifulqi; Rosalina Tjandrawinata; Joko Kusnoto (Wolters Kluwer Medknow Publications, 2021)
Background: Advances in nanotechnology research make the use of cellulose nanocrystals (CNCs) attractive for improving the mechanical properties of glass ionomer cement (GIC). Sugarcane bagasse (Saccharum officinarum L.) is a CNCs source with a high CNC content (72.5%). Objective: This study aimed to determine the effect of the addition of sugarcane bagasse CNCs on the mechanical properties of GIC. Methods: In total, 42 GIC (Fuji IX, GC, Japan) samples were divided into six groups, with various concentrations of CNCs, added to the samples. After 24 h immersion in distilled water at 37°C, the samples were analyzed using the Vickers hardness test. The samples were also characterized by transmission electron microscopy (TEM). For statistical analysis, a one-way analysis of variance, followed by Tukey's post hoc test, was applied. A value of P < 0.05 denoted statistical significance. Results: The TEM revealed crystalline particles in the form of nanocrystals, with varying particle sizes (lengths of 100-200 nm and diameters of 4-19 nm). The addition of 0.4% of CNCS from bagasse fiber to GIC increased the Vickers hardness of the material by 38.89% (P < 0.05). Conclusion: The addition of 0.4% of sugarcane bagasse can improve the hardness of GIC.